Knowledge, Attitude and Practice toward legalization of abortion among female students of Sabiyan secondary and preparatory school, Dire Dawa, Eastern Ethiopia, 2018. A descriptive cross-sectional study - Abera, Legesse; Debebe, Adisalem (Asian Journal of Medical Research, 2020)
Background: Ethiopian abortion law is relatively liberal, but due to lack of knowledge and negative attitude toward legalization of abortion among most women, shortage of safe abortion services provision and significant amount of sociocultural pressures women still go to unsafe abortion service. So the objective of this study was to assess the knowledge, attitude and practice toward legalization of abortion among female students of Sabiyan secondary school, Dire Dawa, March 20-30/ 2018. Subjects & Methods: The study was conducted in Dire Dawa city, in Sabiyan high school. An institutional based cross-sectional survey was employed on randomly selected female students. Data was collected using pre- tested self-administered questionnaire and analyzed using computer software SPSS version 24.0. Tables, graphs and charts were used for some variable to describe the results of the study. Results: A total of 320 regular female students were included making the response rate of 100%. Ethiopian abortion law was assessed only 40 (12.5%) of participants were knowledgeable and only 98 (30.6%) of the respondents were having positive attitude. Out of 24 (7.5%) who ever get pregnant, 15 (4.7%) seek for unsafe abortion and only 7 (2.2%) were having experience (practice) of legal abortion. Conclusion: there was a low level of knowledge of the revised Ethiopian abortion law among study participants and majority of the participants had a negative attitude towards legal abortion services and only few of them had practice of legal abortion. So focusing on awareness creation strategy by each stakeholder is an important.